RUBRAXHANTONE DARI Garcinia forbesii KING. DAN BIOAKTIVITASNYA - Yohannes Alen; Novi Safitri; Dachriyanus -; A. Manaf Ali; N. H. Ladjis; M. V. Sargent (Universitas Andalas, 2008)
ABSTRACT The rubraxhantone compound was isolated firstly from antimicrobial fraction of the bark of Garcinia forbesii King. (Famili Guttiferae) by chromatographic method. The structure of this compound was elucidated based on its spectral data properties. The isolated compound had a significant antimicrobial properties against the selected microbes by diffusion method. Keywords : antimicrobial, Garcinia forbesii King., chromatographic, diffusion method.